Hicret-i Nebî’nin Klasik Türk Şiirine Yansıması - Alvan, Türkan (FSM Vakıf Üniversitesi, 2016)
Arapça kökenli olan hicret kelimesi; “göç etme”, “ayrılma”, “uzaklaşma” anlamına gelir. Hz. Peygamber’in hicreti 26 Safer Perşembe akşamı başlamış, 12 Rebiʿül-evvel Cuma günü ikindi vakti sona ermişti. Hz. Peygamber’in ve Müslümanların Mekke’den Medine’ye hicreti; yapılan zulüm ve baskıların neticesinde davasından vazgeçiş ve yenilgi sonucu bir kaçış değil; aksine geri dönmek üzere kendi iradesiyle Allah için yapılan bir göçtür. Hz. Peygamber’in sünneti olan hicret, vatandan gurbete yolculuktur. Türk Edebiyatında hicretnâmeler yazılmışsa da hicret, genellikle manzum siyer-i nebîler içinde müstakil bir bölüm hâlinde işlenmiştir. Bu çalışmada, Hz. Muhammed’in Hicreti; Klasik Türk Şiirine yansıyan özellikleri ve mazmunlarıyla ele alınacaktır. Ayrıca şiirlerden hareketle hicretin tarihi seyri incelenecektir.

“Hicret” which is originally an Arabic word means “emigration”, “migrate”, “leaving”. “Hicret” of. Muhammed (Peace be Upon Him) started on Thursday Evening, 26th of Safar and ended on Friday Late-Afternoon,12th of Rabee Al-Awwal. The “Hicret” of Muhammed (Peace be Upon Him) and Muslims is not meant to give up the struggle due to cruelity and pressure, or leaving after defeat; but with their own will it is the emigration for Allah to return back. “Hicret” which is sunnah of Rasulullah is the journey from home to a foreign place. Although the “Hicret” was also written in “Hicretname”s in Turkish Literature, it has been written as a separate chapter in the Poems of Prophet’s Life mostly. In this study, the “Hicret” of Hz. Muhammed (Peace be Upon Him) will be addressed with its reflections and “mazmun” onto Classical Turkish Poem. Additionaly, with the help of poems, the journey of “Hicret” will be examined historically.
The Reflection of the Hicret-i Nebi in Classical Turkish Poetry
Keywords: Hicret; Mekke; Medine; Hz. Muhammed; Klasik Türk şiiri; Mecca; Madina; Muhammed (Peace be Upon Him); Turkish poetry